Hadis tentang Lalat yang Jatuh ke dalam Air: Studi Komparatif antara Pemahaman Islam dan Perspektif Kesehatan - Dise Dalusari (Yayasan Albahriah Jamiah Indonesia, 2025)
The hadith about the fly falling into water, as narrated by al-Bukharī, is often debated because it is considered contrary to modern hygiene principles, thus giving rise to an academic need to re-examine its relevance in the context of contemporary health. This study aims to provide a comprehensive understanding of the hadith by examining the authority of the text, the views of classical and modern scholars, and assessing its significance from a scientific perspective. The method used is a qualitative, literature-based research approach with a thematic analysis, which examines the hadith textually and normatively while comparing it with empirical findings from modern microbiology studies. The results of the analysis indicate that some fly species can indeed carry pathogens on their bodies, such as Escherichia coli, Salmonella spp., and Staphylococcus aureus bacteria, which have the potential to cause infectious diseases. However, recent laboratory research has also found that in the bodies of flies, particularly in the wings and cuticle, there are bioactive compounds, including antimicrobial peptides and certain enzymes, that can suppress the growth of pathogenic microorganisms. Several studies have even confirmed that extracts from the fly body have an inhibitory effect on harmful bacterial colonies in in vitro tests, supporting the scientific assumption that other aspects of the fly have therapeutic potential. Thus, these findings indicate that the Prophet’s hadith not only contain normative messages but also have coherence with modern scientific knowledge, further strengthening the hadith’s position as a source of knowledge that does not conflict with science. However, the application of this hadith in contemporary medical practice still requires consideration of caution, the context of hygiene, and the development of modern public health standards. In conclusion, this study highlights the importance of integrating hadith studies and health sciences as a means of enriching contemporary Islamic epistemology, while also creating space for the reinterpretation of hadith through a scientific approach to maintain its relevance in the development of modern medical and religious discourse.